Contrasting Effects of Adipokines on the Cytokine Production by Primary Human Bronchial Epithelial Cells: Inhibitory Effects of Adiponectin - Salvator, Hélène; Grassin-Delyle, Stanislas; Naline, Emmanuel; Brollo, Marion; Fournier, Caroline; Couderc, Louis-Jean; Devillier, Philippe (Frontiers in Pharmacology, 2020)
Abstract BACKGROUND: Obesity is associated with an elevated risk of respiratory infections and inflammatory lung diseases. The objective was to investigate (i) the effects of adipokines (adiponectin (APN), leptin, chemerin, and visfatin) on the production of cytokines by unstimulated and poly(I:C)- and TNF--activated human primary bronchial epithelial cells (hBECs), (ii) the cells’ expression of the APN receptors (AdipoR1 and AdipoR2), and (iii) the cells’ production of APN. METHODS: The hBECs were isolated from patients undergoing surgery for lung carcinoma. The cells were then cultured with human recombinant adipokines in the absence or presence of TNF-or poly(I:C) for 24 h. Supernatant levels of cytokines (IL-6, CCL2, CCL5, CCL20, CXCL1, CXCL8) and APN were measured using ELISAs. The mRNA levels of AdipoR1 and AdipoR2 in hBECs were determined using a real-time quantitative PCR. RESULTS: Of the four adipokines tested, only APN significantly influenced the basal production and the TNF-poly(I:C)-induced production of cytokines by hBECs. APN (3-30 µg.mL-1) was associated with greater basal production of IL-6, CCL20 and CXCL8, lower basal production of CCL2 and CXCL1 and no difference in CCL5 production. APN inhibited the poly(I:C)-induced production of these five cytokines and the TNF--induced production of CCL2 and CXCL1. AdipoR1 and AdipoR2 were both expressed in hBECs. In contrast to human bronchial explants, isolated hBECs did not produce APN. CONCLUSIONS: The APN concentrations are abnormally low in obese individuals, and this fall may contribute to the susceptibility to viral lung infections and the severity of these infections in obese individuals.